The Relationship Between Parents' Knowledge and Vermicular Enterobiasis Incident Rate in Children At Rt. 09/07 Susukan Village in East Jakarta - Muhammad Satrio Prabowo; Ndaru Andri Damayanti; Rika Ferlianti (Junior Medical Journal, 2023)
Background: One of the helminthic diseases that still occurs in Indonesia is worm infection by Enterobius vermicularis. Enterobiasis needs attention because it can cause a decrease in the immune system in children so that it can cause delays in the growth and development of children. Objective: This research was conducted to see the relationship between the incidence of E. vermicularis in children and the level of knowledge of parents. Methods: The method used is quantitative with a cross sectional approach. The anal swab technique is used for the examination of enterobiasis. Parents' knowledge data was collected through interviews with a questionnaire guide. Results: Significantly (p 0.05) 1.7% of enterobiasis in children was found in parents with a lack of hygiene knowledge. Conclusions: There is a correlation between the percentage of enterobiasis in children and their parents' hygiene knowledge.